2021
DOI: 10.3390/ijerph18168373
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Data Reveal Factors Associated with Organised and Non-Organised Colorectal Cancer Screening: An Important Step towards Improving Coverage

Abstract: We investigated factors associated with organised and non-organised colorectal cancer screening using faecal occult blood tests, based on data from 308 municipalities in Flanders (6.6 million residents, 57% of Belgium) during 2015–2017. Logistic regression with generalized estimating equations was used to assess the associations between municipal characteristics and organised and non-organised screening coverages. Factors associated negatively with both organised and non-organised screening: percentage of peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
8
6
2
Order By: Relevance
“…Interestingly, a higher percentage of people with at least 1 general practitioner (GP) visit in last 12 months and people with children have been shown to be associated with lower uptake of both CRC and BC screening (more chances of being in Group 4 vs. Group 1). With regards to GP visits, these results are in contrast with those of a previous study that found that GP visits are positively associated with CRC screening coverage [17]. In this study, however, the association of GP visits and non-organized screening was more pronounced than the association with organized screening.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Interestingly, a higher percentage of people with at least 1 general practitioner (GP) visit in last 12 months and people with children have been shown to be associated with lower uptake of both CRC and BC screening (more chances of being in Group 4 vs. Group 1). With regards to GP visits, these results are in contrast with those of a previous study that found that GP visits are positively associated with CRC screening coverage [17]. In this study, however, the association of GP visits and non-organized screening was more pronounced than the association with organized screening.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that percentages of people with non-Belgian/Dutch nationality and diabetes are associated with a lower probability of screening for CRC (more chances of being in Group 2 vs. Group 1) and BC (more chances of being in Group 3 vs. Group 1). With regards to foreign nationality, these findings are consistent with previous observations at both municipal and individual level [17], [24], [25] and can be explained by the reported perceived language barriers and embarrassment when talking about screening [26]. Moreover, migrants are a high-risk group for limited health literacy and may experience higher difficulties, compared to non-immigrant individuals, in processing health information and translating them it into healthy behaviors [27].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations